2021
DOI: 10.3390/rs13234846
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated CNN Model for Reconstructing and Predicting Land Use/Cover Change: A Case Study of the Baicheng Area, Northeast China

Abstract: Land use and land cover change (LUCC) modeling has continuously been a major research theme in the field of land system science, which interprets the causes and consequences of land use dynamics. In particular, models that can obtain long-term land use data with high precision are of great value in research on global environmental change and climate impact, as land use data are important model input parameters for evaluating the effect of human activity on nature. However, the accuracy of existing reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…The applied approach used in training the prediction model in python 3 for all algorithms was based on LULCC using historical LULC data and both fixed and temporary spatial factors: Machine (SVM) algorithm even after 120 hours of training. This aligns with the findings of a previous study (Zhang et al 2021), where the authors reported that SVM did not yield results even after more than 200 hours of computation. This suggests that SVM is not suitable for large-scale reconstruction and prediction of LULCC, especially when dealing with extensive datasets.…”
Section: Future Lulc Predictionsupporting
confidence: 92%
See 1 more Smart Citation
“…The applied approach used in training the prediction model in python 3 for all algorithms was based on LULCC using historical LULC data and both fixed and temporary spatial factors: Machine (SVM) algorithm even after 120 hours of training. This aligns with the findings of a previous study (Zhang et al 2021), where the authors reported that SVM did not yield results even after more than 200 hours of computation. This suggests that SVM is not suitable for large-scale reconstruction and prediction of LULCC, especially when dealing with extensive datasets.…”
Section: Future Lulc Predictionsupporting
confidence: 92%
“…Specifically, these studies only update the LULC data in the model input for each prediction while keeping the same temporal factors for a specific year. With the exception of the study by (Zhang et al 2021), which considered the temporality of factors, where the process was followed by temporal selection and con-figuration, resulting in a feature database. In comparison, LULC data utilized by this study from 2000 to 2020, in addition to 11 environmental and socio-economic factors that may impact land use changes shown in Population and rainfall variables were generated using the interpolation method known as Inverse Distance Weighting (IDW), expressed as follows:…”
Section: Future Lulc Predictionmentioning
confidence: 99%
“…LULC research has become a global research hotspot [23]. From the analysis of LULC spatial-temporal patterns [24][25][26] and explorations of LULC change driving mechanisms [27,28], the research has evolved to focus on the impact on ecosystem services [29,30], future LULC simulation studies [31][32][33][34], and more detailed analyses of human activities, policies, and other LULC driving mechanisms [35]. In terms of research scale, there have been numerous studies at global, continental, and transnational levels.…”
Section: Introductionmentioning
confidence: 99%